Uvaol Inhibits Inflammatory Response and Prevents Lipopolysaccharide-Induced Acute Lung Injury in Mice - Shi, Yubo; Wang, Airu; Jiang, Hua (Indian Journal of Pharmaceutical Education and Research, 2024)
Background: Sepsis is a clinical disease characterized by systemic inflammatory reactions following infection that can lead to multiorgan failure. Acute Lung Injury (ALI) is a common ailment with increased morbidity and fatality rates worldwide. Objectives: The present investigation was planned to investigate the salutary activities of uvaol against Lipopolysaccharide (LPS)-exposed ALI in mice. Materials and Methods: The 5 mg/kg of LPS was exposed to the mice for 3 days through the intra-tracheal route to initiate the ALI, and 5 and 10 mg/kg, respectively, of uvaol were administered orally for 3 days the LPS challenge. The mice were scarified under anesthesia, lungs were excised, and wet and dry weights were weighed accurately. All the biochemical parameters, including apoptosis, inflammation, and oxidative stress marker levels, were assessed using the respective assay kits. Results: The uvaol (5 and 10 mg/kg) treatment effectively diminished pulmonary edema, total protein, and LDH activity in the ALI mice. The MDA was reduced, and the GSH and SOD levels were increased by the uvaol. The uvaol effectively reduced the inflammatory cytokines and infiltrations in the ALI mice. The PGE-2, iNOS, and COX-2 levels in the BALF of ALI mice were effectively reduced by the uvaol. The Bax and caspase-3 expression was reduced, and the Bcl-2 was elevated by the uvaol. The outcomes of histopathological analysis also supported the therapeutic potential of uvaol against ALI. Conclusion: In conclusion, the outcomes of the current exploration highlighted that uvaol considerably prevented the LPS-exposed ALI in mice via its antioxidant and anti-inflammatory effects. Hence, it can be concluded that uvaol can be employed in the treatment of ALI in the future.
Keywords: Lipopolysaccharide; Cytokines; Apoptosis; Uvaol; Lung edema; Sepsis